Organizational Culture On Employe Performance : Literature Review - Saputra, Muhammad Ajye; ., Sopiah (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The role of Human Resources in the organization plays a very important role in the organization. Employees are an important asset in an organization to manage various tasks within the organization in order to achieve its goals. Employee performance can increase organizational efficiency and effectiveness. This research method uses a literature review, with sources obtained from books and journals. The results of this research indicate that organizational culture has a significant influence on employee performance because of the importance in organizations of using cultural diversity as a strength to increase collaboration, innovation and problem solving. Suggestions for future researchers: this article can be used as a reference for understanding organizational culture on employee performance.